2018
DOI: 10.2196/11308
|View full text |Cite
|
Sign up to set email alerts
|

Audio-/Videorecording Clinic Visits for Patient’s Personal Use in the United States: Cross-Sectional Survey

Abstract: BackgroundFew clinics in the United States routinely offer patients audio or video recordings of their clinic visits. While interest in this practice has increased, to date, there are no data on the prevalence of recording clinic visits in the United States.ObjectiveOur objectives were to (1) determine the prevalence of audiorecording clinic visits for patients’ personal use in the United States, (2) assess the attitudes of clinicians and public toward recording, and (3) identify whether policies exist to guid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(78 citation statements)
references
References 34 publications
4
63
0
Order By: Relevance
“…Ownership of the recording is another issue to consider, for example, the application of HIPAA to recordings made and stored by patients (a non-health entity not subject to HIPAA) and not the health system 11. A lack of policies to guide the recording and sharing of clinical visits needs to be addressed,10 and findings from our project, both quantitative and qualitative, can contribute to this conversation. If managed securely as data in an electronic medical record, recordings could transform healthcare, providing more accurate clinical records and allowing patients and families to revisit medical information that is often forgotten 23…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ownership of the recording is another issue to consider, for example, the application of HIPAA to recordings made and stored by patients (a non-health entity not subject to HIPAA) and not the health system 11. A lack of policies to guide the recording and sharing of clinical visits needs to be addressed,10 and findings from our project, both quantitative and qualitative, can contribute to this conversation. If managed securely as data in an electronic medical record, recordings could transform healthcare, providing more accurate clinical records and allowing patients and families to revisit medical information that is often forgotten 23…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to also consider the privacy and confidentiality implications of recordings, for example, recording and sharing of clinically sensitive conversations and medicolegal concerns of providers. Yet to date, the use of recordings for malpractice suits has not been documented in the small number of clinics where recordings are routinely made available to patients and in at least one case in Arizona, provider participation in recordings may be protective and may result in decreased malpractice premiums 10 11. Ownership of the recording is another issue to consider, for example, the application of HIPAA to recordings made and stored by patients (a non-health entity not subject to HIPAA) and not the health system 11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of consultation recording shown by the studies included in this review might differ from the effects of consultation recording in clinical practice. Patients in the studies included in this review were all provided with a consultation tape, whilst currently patients often bring their own device to a record consultation (Barr et al, 2018). This difference in recording approach could affect the patients' reported outcomes of consultation recording because patients who take the initiative to record their consultation might be more inclined to listen to the recording and might also rate the value of recordings higher.…”
Section: Discussionmentioning
confidence: 99%
“…A commonly used tool to improve recall and understanding is consultation recording (Elwyn, Barr, & Grande, 2015). A survey in the United States has shown that more than one in four physicians ever recorded a consultation for patients' personal use and about one in five of the general public ever recorded a consultation (Barr et al, 2018;Elwyn et al, 2015). Most consultations are recorded in oncology settings (Barr et al, 2018), presumably because of the emotional nature of these consultations.…”
mentioning
confidence: 99%